Collaborative learning via peer editing session: a study on alternative strategy for ESL writing classroom / Sharina Saad …[et al.] - Saad, Sharina; Adzmi, Nor Aslah; Abdul Aziz, Nurazila; Nordin, Razanawati; Bidin, Samsiah (Research Management Institute, 2009)
Academic writing requires students to use higher order thinking skills but most students do not make the effort to respond to teachers’ feedback and think about what they have written in their academic essays. This results in learners producing drafts after drafts with repeated mistakes. Most learners think that assessment and evaluation are the sole responsibility of the teacher. Moreover, most teachers substitute their own words, sentences and even ideas for their students’ errors so these students lose the ownership of their writing. Instead of responding to the teachers’ feedback positively, they build dislike for writing. Therefore, teachers need to make their students realize that their writing is not for their teacher’s eyes only and readership is not limited. By introducing peer editing session after every step in the writing process, learners will widen the readership scope and collaboratively help to think and response to each other’s writing. Similar to children, adolescents such as Universiti Teknologi Mara Kedah students may exhibit these characteristics of a group discussion when they are among peers. In addition, students in peer review groups learn and practice a “language of response" that they can then use to articulate ideas about their own writing. Hence, this research has presented new direction in assessing and responding student’s writing by encouraging the student to work collaboratively through peer editing sessions. While the majority of revisions that students made were surface-level revisions, the changes they made as a result of peer and teacher feedback were more often meaning-level changes than those revisions they made on their own. It was also found that writing multiple drafts resulted in overall essay improvement.